Analysis of The Effect of Government Expenditure and GRDP on Provincial Tax Revenue in Indonesia, 2014–2023 - Sintia Neno Maitasya; Fia Shofiyatun; Friyanedo Wahyu Achmadi; Adinda Trias Ananta; Nabila Putri Zakariya; Talia Rahma Fadila; Puspa Dwi Hartatik (Buletin Ekonomika Pembangunan, 2026)
This study aims to analyze the effect of government spending and Regional Domestic Product (RDP) on tax revenue in Indonesia during the period 2014-2023. The study uses a quantitative approach with a panel data model covering 34 provinces in Indonesia. The analysis was conducted through Chow tests, Hausman tests, and Lagrange Multiplier tests to determine the best model, and the results showed that the most appropriate model was the Random Effect Model (REM). The estimation results showed that government spending had a positive and significant effect on tax revenue, while GRDP had a negative and insignificant effect. Simultaneously, both variables have a significant effect on tax revenue with a coefficient of determination of 42.29%. These findings indicate that an increase in public spending, especially in the productive sector, can strengthen the government's fiscal capacity, while economic growth through GRDP is not fully reflected in an increase in tax revenue. Keywords: Government Expenditures, Gross Regional Domestic Product (GRDP), Tax Revenue, Fiscal Policy, Public Expenditure Efficiency, Regional Economic Growth, Panel Data Regression, Random Effect Model (REM)